Spiritual Development in Family Management - U Tun Aung, Maulana Akbar Shah @ (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
In Islam, spirituality means worshipping God, seeking the satisfaction of God, awareness of the origin of the universe, humility, submission, and trust, which man demonstrates in all of his actions. In this way, an individual's oath to Allah is the focal point of Islamic spirituality. When discussing the role of spirituality in touching the unending episode of happiness in this world and the next world, the nature of spirituality continues to develop beyond one’s imagination. The word "spiritual" comes from the Latin word "spiritus," indicating breath, an essential element of human life. Without breathing, there is no life; therefore, every aspect of living, in essence, is related to the realm of the spiritual. Spirituality is also essential in human life experiences through the physical and mental senses, which are difficult to express in ordinary language. They have something to do with deep knowledge, dealing with living and non-living things and the metaphysical. Searching for a true sense of spirituality could show a path to self-identity that can answer who we are, where we come from, and our destination. This paper discusses the significance of the development of spirituality, starting from an individual to the family and society. It provides methods of developing spirituality, the nature of the development of spiritual values, training the children with the inculcation of religious teachings, and a comparison of spiritual values in Islamic and western practices. This research applies the descriptive-analytical method. It attempts to illustrate the significance of applying spirituality in the family and society at large as a catalyst towards the prosperity of this world and the next.